Estudio de prefactibilidad para la instalación de una empresa productora de mayonesa a base de Persea americana Hass - Minaya Henostroza, Karla Ivette (2020)
Peru has seen an impressive growth in the consumption of products of national origin, its quality and good taste is not only attractive to us Peruvians but also to foreigners who have become our faithful admirers. In the case of our country, considering its agricultural diversity, it is convenient to think about elaborating a product that allows the agro industrial and economic development of the country. That is why the following preliminary study will use all the tools of industrial engineering to analyze the feasibility of this project to determine if it is feasible and economically profitable to implement a mayonnaise producer company based on avocado. An annual demand of 1 489 802 units is projected for the fifth year of the project. The target market is the economic sector A and B, who lives in Metropolitan Lima and those who are interested in consuming healthy products. The industrial plant has an annual capacity of 1 510 760 units per year, a minimum area of 426,85 m² and is located in Lurín district. The production process consists of scalding and rapidly cooling the avocado to avoid the process of enzymatic browning, pulping, mixing all the ingredients and emulsifying to obtain the final product to be packed in 500 g doypack bags. Finally, through the economic-financial evaluation and with an initial investment of S/ 2 489 335,17 which 60% will be financed by a bank and 40% own capital, so it is concluded that the execution of the project is profitable, given that there are positive values in VANE S/ 468 487 and VANF S/ 494 414 with a TIRE value of 18,87% and a TIRF of 26,7%, these being higher than the opportunity cost (COK = 12,84%).